2022
DOI: 10.3389/fnut.2022.992733
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin for COVID-19 prevention, treatment, and recovery

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), a unique beta-coronavirus, has caused the most serious outbreak of the last century at the global level. SARS-CoV-2 infections were firstly reported in the city of Wuhan in China in 2019 and this new disease was named COVID-19 by World Health Organization (WHO). As this novel disease can easily be transmitted from one individual to another via respiratory droplets, many nations around the world have taken several precautions regarding the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…LTF improves neurological deficits associated with stroke (62). Accumulating evidence has revealed the potential applications of LFT in the COVID-19 management (63)(64)(65). Targeting LTF may be a treatment strategy for COVID-19 and IS.…”
Section: Discussionmentioning
confidence: 99%
“…LTF improves neurological deficits associated with stroke (62). Accumulating evidence has revealed the potential applications of LFT in the COVID-19 management (63)(64)(65). Targeting LTF may be a treatment strategy for COVID-19 and IS.…”
Section: Discussionmentioning
confidence: 99%
“…It has antibacterial, antiviral, antifungal, antiparasitic, and anti-inflammatory properties, as well as being implicated in innate and adaptive immune modulation ( 42 , 43 ). Lf has antiviral activity against DNA and RNA viruses ( 44 , 45 ), and the exact mechanism of its activity against bacterial and viral infections has been highlighted for the prevention of diseases ( 46 ).…”
Section: The Main Immunomodulating and Bioactive Components Of Bovine...mentioning
confidence: 99%
“…Besides, immunomodulatory drugs such as lactoferrin is used to control inflammatory responses in their respective auto-immune conditions, which was demonstrated its effects and mechanisms in the prevention, treatment, and recovery for COVID-19 ( 9 ). A clinic trial of lactoferrin suggested that, the COVID-19 patients who were given lactoferrin every day for 10 days, had shown a positive effect and all patients had a faster recovery when compared with the control group ( 10 ). Furthermore, traditional Chinese medicine (TCM) was also exerted the prevention and treatment in regulating immunity and inflammation during the outbreak of COVID-19.…”
Section: Introductionmentioning
confidence: 99%